2018
DOI: 10.1186/s13065-018-0439-9
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis, and antimicrobial and anticancer activities of some pyridines, thioamides, thiazole, urea, quinazoline, β-naphthyl carbamate, and pyrano[2,3-d]thiazole derivatives

Abstract: BackgroundChalcones have a place with the flavonoid family and show a few very important pharmacological activities. They can used as initial compounds for synthesis of several heterocyclic compounds. The compounds with the backbone of chalcones have been reported to possess various biological activities.ResultsPyridine and thioamide derivatives were obtained from the reaction of 3-(furan-2-yl)-1-(p-tolyl)prop-2-en-1-one with the appropriate amount of malononitrile, benzoylacetonitrile, ethyl cyanoacetate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Antibacterial activity of the compounds was screened by using the disk-diffusion method [ 51 ]. In this study, inhibition of bacterial growth was investigated against Gram-positive bacteria Bacillus subtilis and Gram-negative bacteria Escherichia coli .…”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial activity of the compounds was screened by using the disk-diffusion method [ 51 ]. In this study, inhibition of bacterial growth was investigated against Gram-positive bacteria Bacillus subtilis and Gram-negative bacteria Escherichia coli .…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy is frequently combined with surgery or radiation therapy. Most chemotherapeutic drugs are anthracycline, plant alkaloids, antimetabolites, monoclonal antibodies, topoisomerase inhibitors, or other antitumor agents [ 4 , 5 , 6 , 7 , 121 , 122 , 123 , 124 , 125 , 126 ]. Even though various types of chemotherapeutic drugs have been developed recently, only very few drugs have led to complete recovery in cancer patients [ 9 , 127 , 128 ].…”
Section: Liquid Crystal Chemotherapeutic Drugs For the Treatment Omentioning
confidence: 99%
“…The last years of the research have confirmed that thiazole scaffold has diverse biological properties that can be used to treat many diseases, such as microbial infections (Bikobo et al 2017;Secci et al 2012;Łączkowski et al 2018a, 2018bZaki et al 2018;Ansari et al 2018), Parkinson's disease (Carradori et al 2018), cancer (de Santana et al 2018;Łączkowski et al 2014, 2016a, 2016bPiechowska et al 2019;Gomha et al 2018), epilepsy (Siddiqui and Ahsan 2010;Ahangar et al 2011;Łączkowski et al 2016a, 2016b, toxoplasmosis (Schultz et al 2014;Łączkowski et al 2018a, 2018b, and antioxidants (Geronikaki et al 2013;Djukic et al 2018). Considering the above-mentioned findings, we decided to design and synthesize the structure of hybrids incorporating both the thiazole ring and the cyclohexenyl moiety.…”
Section: Introductionmentioning
confidence: 98%